Sympathetic neurons are a powerful driver of myocyte function in cardiovascular disease - Larsen, H; Lefkimmiatis, K; Paterson, D (Springer Nature, 2016)
Many therapeutic interventions in disease states of heightened cardiac sympathetic activity are targeted to the myocytes. However, emerging clinical data highlights a dominant role in disease progression by the neurons themselves. Here we describe a novel experimental model of the peripheral neuro-cardiac axis to study the neuron’s ability to drive a myocyte cAMP phenotype. We employed a co-culture of neonatal ventricular myocytes and sympathetic stellate neurons from normal (WKY) and pro-hypertensive (SHR) rats that are sympathetically hyper-responsive and measured nicotine evoked cAMP responses in the myocytes using a fourth generation FRET cAMP sensor. We demonstrated the dominant role of neurons in driving the myocyte ß-adrenergic phenotype, where SHR cultures elicited heightened myocyte cAMP responses during neural activation. Moreover, cross-culturing healthy neurons onto diseased myocytes rescued the diseased cAMP response of the myocyte. Conversely, healthy myocytes developed a diseased cAMP response if diseased neurons were introduced. Our results provide evidence for a dominant role played by the neuron in driving the adrenergic phenotype seen in cardiovascular disease. We also highlight the potential of using healthy neurons to turn down the gain of neurotransmission, akin to a smart pre-synaptic ß-blocker.